The Shift Premium: Evidence from a Discrete Choice Experiment - Sam Desiere; Christian Walter (Institute of Labor Economics (IZA), 2023)
Shift work is a widespread but understudied phenomenon. This paper examines one specific aspect of shift work: the shift premium. To this end, we included a discrete choice experiment in an online survey targeted at night and shift workers. Respondents chose between a standard 9 am - 5 pm job paying exteuro15 per hour and a job with shift work in which the wage randomly varied between exteuro12 and exteuro20. The results show that respondents demand sizeable shift premiums to prefer shift over daytime work, with higher premiums for more onerous working hours such as night shifts or rotating shifts. We observe substantial heterogeneity in the shift premium across respondents and provide suggestive evidence of labour market sorting.
Keywords: C91; J31; J48; 330; shift work; shift premium; Willingness to Pay; discrete choice experiment